Comparative assessment of a COVID-19 vaccine after technology transfer to Iran from critical quality attributes to clinical and immunogenicity aspects - Delaram Doroud; Mona Sadat Larijani; Alireza Biglari; Fatemeh Ashrafian; Talieh Sabouni; Sana Eybpoosh; Vicente Verez-Bencomo; Yury Valdés-Balbín; Dagmar García-Rivera; Yaneli Herrera-Rojas; Yanet Climent-Ruiz; Darielys Santana-Mederos; et al. (Scientific Reports)
Abstract During COVID-19 pandemic, international pharmaceutical companies put effort to build global manufacturing networks for vaccines. Soberana Plus vaccine, a recombinant protein based vaccine (RBD dimer), with the trade name of PastoCovac Plus in Iran, is based on a protein subunit platform in Cuba and completed preclinical and toxicological assessments. This study aimed at presenting the steps of vaccine technology transfer from Cuba to Iran. This study provides the first practical comparability results in Iran to ensure the quality, safety and efficacy of a protein subunit vaccine against COVID-19 after a successful technology transfer from Cuba. PastoCovac Plus was transferred to Iran at the formulation stage. The assessment of the active ingredient pharmaceutical (API) was achieved through physicochemical and clinical data collection and tests to assure if there was any adverse impact on the vaccination results. In order to assess the quality of the vaccine product after technology transfer, we sought different properties including regulatory features, physicochemical quality, vaccine potency and stability as well as its immunogenicity and safety. Following the evaluation of the clinical quality attributes (CQAs) based on the standard protocols, the results showed that the two vaccines are highly similar and comparable, with no considerable effect on safety or efficacy profiles. The CQAs were all in the acceptance limits in terms of safety and efficacy as well as clinical evaluation results. The immunogenicity evaluation also confirmed no significant differences between the vaccines regarding reinfection (P = 0.199) or vaccine breakthrough (P = 0.176). Furthermore, the level of anti-spike and neutralizing antibodies in the both vaccine groups was not significantly different indicating the equality of performance between the two vaccines. According to the results of the quality and clinical assessment of this study, we achieved an acceptable quality attributes and acceptant limits in terms of safety and efficacy of the vaccines pre and post technology transfer.